Inhibition of coronaviral exoribonuclease activity by TRIM-mediated SUMOylation - Kannan Balakrishnan; Surajit Chakraborty; Cindy Chiang; Caleb M. Stratton; Shanti Pandey; Anna A. Tumanova; Shaun K. Olsen; Michaela U. Gack (Proceedings of the National Academy of Sciences, 2026)
Members of the TRIM E3 ligase family are effectors of the host innate or intrinsic defense against various viruses; however, how specific TRIM proteins antagonize coronavirus infection is still largely elusive. Through an RNAi screen targeting 71 human TRIM genes, we identified multiple TRIM proteins with antiviral or proviral activity against SARS-CoV-2. TRIM32 potently restricted SARS-CoV-2 replication in a RING E3 ligase-dependent but interferon-independent manner. Mechanistically, TRIM32 binds to and SUMOylates the 3′‐to‐5′ exoribonuclease (ExoN) of Nsp14, an enzyme essential for SARS-CoV-2 replication. TRIM32-mediated Nsp14 SUMOylation at K9 and K200 inhibits RNA binding and Nsp10 cofactor recruitment, respectively, ultimately suppressing ExoN activity. Our study further revealed that Nsp14 SUMOylation by TRIM32 and its antiviral activity are broadly conserved for coronaviruses. These results identify the coronaviral Nsp14 protein as a direct target of host restriction via SUMOylation, which may uncover ways to therapeutically inhibit coronavirus infections in humans.